Unveiling the Nexus: Analyzing foreign direct investment and energy consumption in shaping carbon footprints across Africa’s leading CO2-emitting countries - Njie, Yahya; Wang, Weidong; Liu, Lin; Abdullah, . (International Journal of Renewable Energy Development, 2024)
Carbon emissions have become a pressing global concern because of its contribution to climate change and environmental degradation. Given the urgency to tackle climate change, especially by reducing carbon emissions, this study focuses on Africa’s leading CO2 emitters from 2000 to 2020. The aims of the study are; to examine whether there is evidence of an energy-Kuznets Curve among the leading CO2 emitters in Africa, to examine whether there is evidence of an FDI-Kuznets Curve among the leading CO2 emitters in Africa, and to Identify the turning points. The study employs an innovative analysis of unbalanced panel data utilizing sophisticated econometric techniques, the contemporaneous correlation methodology, which are; the feasible generalized least squares (FGLS), and the panel-corrected standard errors (PCSE) to uncover insights. The results reveal consistency across all employed techniques. The study confirms the existence of an Energy-Kuznets Curve among the leading CO2 emitters in Africa; it also finds evidence of a U-shaped relationship between foreign direct investment and carbon emissions among the leading CO2 emitters in Africa; finally, it also identifies crucial turning points at 2760.12kg and 2886.29kg of oil equivalent per capita for energy use and 6.89% and 6.17% for FDI inflow, respectively. By investigating the factors influencing carbon emissions and evaluating their impacts, our study offers valuable insights for policymakers. These findings can inform the development of targeted interventions to curb emissions intensity, enhance energy efficiency, and foster the adoption of renewable energy sources.